The cost of re-synchronization in a leaf-cutter ant colony - Mila Maria Pamplona-Barbosa; Marcelo Arruda Fiuza de Toledo; Gisele Akemi Oda; André Frazão Helene (Communications Biology)
Abstract Biological rhythms are essential components of organisms’ physiology and behavior. In social insects, biological rhythms can be studied at varying levels of a colony, revealing interesting aspects about how rhythms arise from the individual and collective levels. Here, by developing a video-tracking software based on machine learning techniques, we investigated the emergent collective rhythms of a leaf-cutter ant colony under laboratory conditions. The colony displayed rhythmic, daily foraging activity, with most of its foraging occurring during the dark phase of the day. The same pattern is found in the leaf-cutting activity. After being exposed to a 6-hour phase shift of the light-dark cycle, the daily rhythm of colony activity resynchronized with the new cycle phase after a few transient days. During these transient days, an increase in its daily leaf intake was measured. Under synchronized conditions, the ratio between foraging and leaf intake of the colony was higher during the light phase and decreased in the transient days after the phase shift, revealing that temporal synchronization plays an important role in the organization of the colony. Our findings illustrate the dynamic aspects of temporal synchronization in complex eusocial systems, pointing to these systems as exciting new models for comparative research.